Tympanomastoidectomy: comparison between canal wall-down and canal wall-up techniques in surgery for chronic otitis media - Azevedo,Alexandre Fernandes de (2013)
INTRODUCTION: Chronic otitis media (COM) is an inflammatory condition associated with otorrhea as well as large and persistent perforations of the tympanic membrane in some cases. COM can also lead to cholesteatoma. Surgical treatment with canal wall-down and canal wall-up tympanomastoidectomy is considered for both types of illness. The choice of technique is controversial and is dependent on several factors, including the extent of disease. OBJECTIVE: We aimed to evaluate surgical outcomes in COM patients with and without cholesteatoma treated with canal wall-down and canal wall-up tympanomastoidectomy. Disease eradication and post-operative auditory thresholds were assessed. METHOD: Patient records from the otorhinolaryngology department of a tertiary hospital were assessed retrospectively. RESULTS: Patients who underwent canal wall-up tympanomastoidectomy had a higher rate of revision surgery, especially those with cholesteatoma. However, there were no statistically significant differences in post-operative hearing thresholds between the two techniques. CONCLUSION: The canal wall-down technique is superior to the canal wall-up technique, especially for patients with cholesteatoma.